SINERGITAS SATUAN POLISI PAMONG PRAJA DAN BEA CUKAI DALAM PEMBERANTASAN PEREDARAN ROKOK ILEGAL DI KABUPATEN TEGAL PROVINSI JAWA TENGAH - Hurul Aini Syalfa Harbiyah Razak,; Lalu Satria Utama, (Journal of Innovation Research and Knowledge, 2025)
The distribution of illegal cigarettes in Tegal Regency is a serious concern for the Tegal Regency Government because of the negative impacts it has on state revenues and community welfare. This has encouraged the local government to try to distribute illegal cigarettes to its members. One of the steps taken is to build cooperation between the Civil Service Police Unit and Customs. Objective: This study aims to determine the synergy between the Civil Service Police Unit and Customs in eradicating illegal cigarettes in Tegal Regency. Method: The research method used is descriptive qualitative using the synergy theory by Najiyati and Rahmat (2011), with data collection through interviews, observations, and documentation from various sources, including Civil Service Police Unit and Customs officials, business actors, the community, and related documents. This study uses data analysis techniques, starting from data collection, data reduction and data presentation, and drawing conclusions. Results/Finding: The results of the study indicate that the synergy between the Civil Service Police Unit and Customs in eradicating the distribution of illegal cigarettes in Tegal Regency is not optimal. The indicators that are the benchmark for the success of the synergy have been implemented and measured well, but there are still obstacles or barriers both from within the organization and from outside the organization. Conclusion: The synergy between Satpol PP and Tegal Regency Customs is still not optimal. Therefore, future illegal cigarette eradication operations need to be considered more comprehensively, by considering various related aspects